Konstitusionalitas Perjanjian Distribusi dalam Persaingan Usaha Sehat - Yati Nurhayati (The Constitutional Court of the Republic of Indonesia, 2011)
Distribution agreement that contains the agency agreement if the terms of law no.5, the year 1999 concering Prohibition of Monopolistic Practices and Unfair Business Competition can be categorized as a distribution agreement if the basic agreement between the parties is a purchase agreement so that he acts on his own name so that can have the freedom to set prices of goods or services that have been bought.In practice in Indonesia,distribution agreement have a variety of different shapes and substances in accordance with the will of the parties,so that in determining whether the agreement included an agreement that made the distribution or agency agreement should be seen from the substance of the agreement